Plant availability of trace elements in sewage sludge-treated soils: methodology¹ - Marchi,Giuliano (2011)
Synthetic root exudates were formulated based on the organic acid composition of root exudates derived from the rhizosphere of aseptically grown corn plants, pH of the rhizosphere, and the background chemical matrices of the soil solutions. The synthetic root exudates, which mimic the chemical conditions of the rhizosphere environment where soil-borne metals are dissolved and absorbed by plants, were used to extract metals from sewage-sludge treated soils 16 successive times. The concentrations of Zn, Cd, Ni, Cr, and Cu of the sludge-treated soil were 71.74, 0.21, 15.90, 58.12, and 37.44 mg kg-1, respectively. The composition of synthetic root exudates consisted of acetic, butyric, glutaric, lactic, maleic, propionic, pyruvic, succinic, tartaric, and valeric acids. The organic acid mixtures had concentrations of 0.05 and 0.1 mol L-1 -COOH. The trace elements removed by successive extractions may be considered representative for the availability of these metals to plants in these soils. The chemical speciation of the metals in the liquid phase was calculated; results showed that metals in sludge-treated soils were dissolved and formed soluble complexes with the different organic acid-based root exudates. The most reactive organic acid ligands were lactate, maleate, tartarate, and acetate. The inorganic ligands of chloride and sulfate played insignificant roles in metal dissolution. Except for Cd, free ions did not represent an important chemical species of the metals in the soil rhizosphere. As different metals formed soluble complexes with different ligands in the rhizosphere, no extractor, based on a single reagent would be able to recover all of the potentially plant-available metals from soils; the root exudate-derived organic acid mixtures tested in this study may be better suited to recover potentially plant-available metals from soils than the conventional extractors.